Lactobacillus acidophilus ATCC 4356 Alleviates Renal Ischemia–Reperfusion Injury Through Antioxidant Stress and Anti-inflammatory Responses and Improves Intestinal Microbial Distribution - Zhang, Peng; Han, Xiuwu; Zhang, Xin; Zhu, Xuhui (Frontiers in Nutrition, 2021)
Background: Ischemia–reperfusion injury (IRI) is one of the main causes of acute kidney injury. Our previous results have shown that anti-oxidative stress decreased in the renal IRI model. This study aimed to investigate the effect of Lactobacillus acidophilus ATCC 4356 on oxidative stress, inflammation, and intestinal flora in renal IRI. Methods: The model of renal IRI was established by cross-clamping the renal pedicle with non-traumatic vascular forceps. H&E staining was applied to observe the damage of kidney tissue in each group. The concentrations of serum blood urea nitrogen (BUN), creatinine (Cre), superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA) were detected by biochemical kit. ELISA measured the concentrations of interleukin (IL)-1β, IL-8, IL-4, and IL-10. qRT-PCR was performed to detect molecular expressions of ATCC 4356, oxidative stress-related factors [nuclear factor-related factor 2 (Nrf2), heme oxygenase 1 (HO-1)], inflammatory factors [tumor necrosis factor (TNF)-α, IL-1β, IL-8, interferon (IFN)-γ, IL-4, IL-10], and apoptosis-related factors [caspase 3, Bax, Bcl2, high-mobility group box protein 1 (HMGB1)]. Except for ATCC 4356, the protein expression of the above indicators was detected by Western blot. The apoptosis level of renal tissue cells was detected by TdT-mediated dUTP nick end labeling (TUNEL). 16S rDNA gene sequencing was used to detect the changes of microbial species in the contents of the duodenum and screen out the differentially expressed flora. Results: Both the glomeruli and renal tubules of ischemia/reperfusion (I/R) mice were severely damaged. H&E result displayed that L. acidophilus ATCC 4356 attenuated the infiltration of inflammatory cells caused by I/R. ATCC 4356 reduced the high expression of BUN and Cre in I/R mice with a dose effect. It also reduced the high expression of MDA, TNF-α, IL-1β, IL-8, IFN-γ, caspase 3, Bax, and HMGB1 in I/R mice, while it increased the low expression of SOD, GSH, Nrf2, HO-1, IL-4, IL-10, and Bcl2 in I/R mice. ATCC 4356 inhibited the high level of apoptosis in the kidney tissue of I/R mice. In IRI mice, the top 3 different gut microbiota were Helicobacter, cultivated_bacterium, and k__Bacteria_ASV_3 compared with sham mice. Oral L. acidophilus ATCC 4356 reversed this change. Conclusion:L. acidophilus ATCC 4356 attenuated renal IRI through anti-oxidative stress and anti-inflammatory response and improved the intestinal microbial distribution.